Exposure to Chinese famine in early life and the risk of multimorbidity in adulthood - Jiahui Zhang; Le Zhang; Wenyan Wu; Xiaowei Zheng (BMC Public Health)
Abstract Objectives Previous studies had reported the association between famine exposure in early life and subsequent non-communicable diseases risk. In current study, we aimed to evaluate the associations between famine exposure on multimorbidity prevalence and incidence in middle-aged and older Chinese population. Methods A total of 13,254 participants from the China Health and Retirement Longitudinal Study 2011 were included in cross-sectional analyses. 5,780 participants were including in longitudinal analyses and were followed up in 2020. Based on the questionnaire, participants were divided into non-exposed, mild famine, moderate famine and severe famine subgroups. Results In cross-sectional analyses, both mild, moderate and severe famine groups were significantly associated with higher multimorbidity prevalence. During the 9 years of follow-up, a total of 2,643(45.73%) participants with multimorbidity incident were identified. After adjusting for all covariates, individuals who experienced mild famine, moderate famine and severe famine were significantly associated with increased risk of multimorbidity incident, with the corresponding ORs (95%CI) being 1.32(1.14–1.52), 1.54(1.21–1.96) and 1.62(1.32–1.99), respectively. Discussion Our findings indicate that famine exposure in mild, moderate and severe famine groups might be associated with an increased multimorbidity risk.